Microbial Community Dynamics and Natural Fermentation Profiles of Ensiled Alpine Grass Elymus nutans Prepared From Different Regions of the Qinghai-Tibetan Plateau - Ding, Zitong; Bai, Jie; Xu, Dongmei; Li, Fuhou; Zhang, Yixin; Guo, Xusheng (Frontiers in Microbiology, 2020)
Feed deficiency during the long cold period of a year is one of the major problems that the traditional year-round animal grazing system has faced on the Qinghai-Tibetan plateau (QTP) since ancient time. Therefore, ensiling the grasses from grassland could be a desirable feeding regime to preserve high quality forage and to alleviate the seasonal unbalanced feed supply problem on this plateau. The present study was designed to investigate dynamics of bacterial community and natural fermentation quality of ensiled Elymus nutans collected from grasslands in four different areas with different elevations [Tianzhu County (TZ), 2965 m; Golog Prefecture (GL), 3763 m; Damxung County (DX), 4228 m, and Nagqu Prefecture (NQ), 4752 m] on the QTP. The bacterial community was characterized by using the PacBio single molecule with real-time sequencing technology (SMRT). The harvested fresh E. nutans grasses were ensiled in vacuum-sealed polyethylene bags for 14, 30, 60, and 90 days. Obvious differences in the epiphytic bacterial community of the fresh E. nutans samples from the four areas were observed, which resulted in various bacterial community dynamics and fermentation qualities of ensiled E. nutans. Higher fermentation quality was observed in silage samples from Nagqu than in those from the other areas (P < 0.05). Lactic acid bacteria (LAB) involved in fermentation of E. nutans from low altitude areas consisted of Pediococcus pentosaceus, Lactobacillus sp., Leuconostoc mesenteroides, and Lactobacillus coryniformis, whereas major LAB species involved in the fermentation of E. nutans silage from high altitudes included L. mesenteroides, Lactobacillus brevis, and Lactobacillus sp. Correlation analysis between bacterial composition and fermentation quality of E. nutans silages made from the four different areas in the QTP indicated that the LAB species responsible for silage fermentation in different areas were totally different, which was mainly due to the different epiphytic bacterial compositions in fresh E. nutans before ensiling. The present results provide important information on revealing the bacterial communities and fermentation quality of ensiled E. nutans, and on future screening of LAB isolates for making high quality silage in order to alleviate feed shortage of the traditional year-round grazing system on the QTP.